High-Resolution Household Load Profiling and Evaluation of Rooftop PV Systems in Selected Houses in Qatar - Omar Alrawi (18060856) (2019)
Even though Qatar’s per capita electricity consumption is one of the highest in the world, little is currently known about behind-the-meter power consumption. The residential sector is the largest consumer of electricity, accounting for approximately 59% of the overall consumption of electricity. As energy subsidies lead to budget deficits and overconsumption of carbon resources, there is a pressing need to examine the residential load profile to better understand consumption patterns and uncover potential solutions for more efficient usage. Residential load profiles are typically influenced by seasonal and socio-economic factors. Furthermore, household load profiles can be used to examine the viability of rooftop photovoltaic (PV) systems. In this study, a total of 10 houses in Qatar were chosen, and their power demand was monitored for over a year using smart energy monitors. This empirical research was conducted to achieve the following goals: (1) creation of the first high-resolution residential load profiles in Qatar and in the Gulf region; (2) analyses of the acquired load profiles and the determining factors that affect energy consumption; and (3) calculation of self-consumption values, analysis of the viability of household rooftop PV systems, and discussing potential use-cases for energy storage systems. Investigation of this topic is particularly important for Qatar as the country is adopting a sizable portion of PV systems (5% by 2021) and promotes sustainable energy options as a part of a national development strategy. Results show that there are significant differences between per-household and per-capita consumption due to factors such as electricity subsidies, household income and size, and air-conditioner type. Moreover, due to high electricity consumption, distributed energy storage units for bill management applications have limited applicability with current pricing tariffs. To the best of authors’ knowledge, this is the first study conducted in Qatar and in the Gulf region where a growing amount of interest is given to measure and improve building energy performance. Other Information Published in: Energies License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/en12203876